海氷内部における炭酸カルシウム結晶（イカイト）の析出メカニズム - 野村, 大樹; 中島, 遥香; Daiki, Nomura; Haruka, Nakajima (2017)
第8回極域科学シンポジウム/個別セッション：[OM] 極域気水圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OM] Polar Meteorology and Glaciology Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object